Strongyloides hyperinfection diagnosed by bronchoalveolar lavage in a university medical center in South America. Cases report (2013)
Immunocompromised patients are at high risk of oportunistic infections, Strongyloides hyperinfection is one of them and can be diagnosed with bronchoalveolar lavage (BAL). Aim: We described clinical characteristics, risk factors and clinical outcomes of immunocompromised patientes with Strongyloides stercoralis hyperinfection (SSH). Patients and methods: Between 2001 -2012, nine consecutive cases of Strongyloides stercoralis hyperinfection with positive bronchoalveolar lavage were analyzed.